Pasantías y su influencia en el desarrollo de las competencias laborales en los estudiantes del bachillerato general unificado de la Unidad Educativa San Juan, canton Pueblo Viejo, provincia de los Ríos. - Cercado Mayorga, Benny Xiomara (2017)
The present investigative work is based on internships and their influence on the development of labor competencies, obtaining as a result the institutional contribution that allows enhancing each one of the formative activities in the students, the same that allow to acquire new knowledge in the work environment. For a good internship the teacher should encourage, train students about the work done in an institution or company and thus prepare students before leaving to it. The conclusion of this research determines the contribution of the internships in the labor and institutional, it is of great importance to promote the skills to be developed in the internships and in such a way to improve the work environment.